Register Periklanan - Widowati, Heningtyas (Institut Seni Indonesia Yogyakarta, 2010)
The Registerin Advertising. Register is one of the language variations determined by certain occupational or social groups. The most obvious difference in register is shown by the lexical discrepancy. A same word may have different meaning when it is used in distinct profession. The meaning of each word usage in each occupational field can be comprehended when it is used in context. This study aim at describing the register, in terms of lexical variation, in advertisingfield. The analysis on the data gathered indicates that: first, grammatically the words used come from English that are either borrowed, adapted, or translated into Indonesian. This fact resulted in the occurance of word derivation process by employing Indonesian grammar rule to the English words. Second, the meanings of the advertising registers are close to the meanings of the terms used in the fields offine art, communication, and commerce. Finally, those registers can be at least classified into four class namely types of advertisement, technical terms, professional position, and types of media. Keywords: Register, occupational field, advertising.